Implementation of Norm-referenced Assessment and Benchmark Assessment in Processing Learning Outcomes of Students in Grade X SMAIT Putri AL Hanif Cilegon - Atika Puji Lestiyani; Tatu Hilaliyah (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
This study aims to examine the application of Norm-referenced Assessment (PAN) and Benchmark Assessment (PAP) in processing the Indonesian language learning outcomes of students at SMAIT Putri Al Hanif Cilegon. A qualitative approach with an interactive case study method was used. Teachers were identified as the primary data sources, while related documents served as supporting data. Data analysis followed the Miles and Huberman method, which includes three stages: data reduction, data presentation, and data verification. The findings reveal that SMAIT Putri Al Hanif applies both evaluative approaches during midterm assessments to periodically measure students' progress and achievements in Indonesian language learning. This demonstrates the school's commitment to providing holistic and measurable assessments, enriching the Indonesian learning process. However, this study has limitations, particularly in the research timeline. It only evaluates a few factors influencing the quality of midterm exam scores for 10th-grade students, leaving room for further research to explore other unexplored factors. Conclusions are drawn based solely on the available data analysis, emphasizing the need for future studies to adopt different methods, broader samples, and more comprehensive research instruments. The author hopes that future research can more comprehensively and efficiently manage and evaluate student outcomes from both formative and summative assessments. Teachers, as evaluators, must understand learning outcome processing techniques to minimize unfairness in student assessment. This study offers valuable insights into evaluation practices and provides a foundation for developing more effective assessment methods in Indonesian language teaching.